Indian Diabetes Risk Score (IDRS): An effective tool to screen undiagnosed diabetes - Anand, Komal; Jain, Seema; Chopra, Harivansh; Kumar, Arun; Singh, Ganesh (Indian Journal of Community Health, 2022)
Background: Diabetes is an insidious public health problem. India has the second largest number of adults living with diabetes worldwide (77 million). Indian Diabetes Risk Score (IDRS) is a simple, cost-effective and feasible tool for mass screening programme at community level. Aim & Objective: To assess diabetes risk in adults aged 30 years and above and to identify high risk subjects for screening undiagnosed diabetes in an urban population of Meerut. Settings and Design: Community based cross-sectional study. Methods and Material: All adults who were ?30 years of age and non-diabetic were interviewed using pre-designed, pre-tested questionnaire for their socio-demographic profile and lifestyle. Fasting Blood glucose of all study subjects were done to screen undiagnosed diabetics. Statistical analysis used: Centers for Disease Control (CDC), Epi Info TM 7.2.3.1 was used. Pearson’s Chi Square were applied. Results: 33.4% were found to have high diabetes risk. Risk of diabetes increases with age. 7.6% of the study subjects were found to be diabetic and were unaware of their diabetic status. Physical inactivity and increasing waist circumference were found to be significantly associated with risk of diabetes. Diabetes risk was also significantly associated with positive family history. Conclusions: Screening and early identification of high risk individuals would help in early diagnosis and treatment to prevent or to delay the onset of diabetes mellitus and its complications.